Arterial thrombosis: Going, gone! - Gardiner, E.; Berndt, Michael (American Society of Hematology, 2010)
Most antithrombotic approaches target prevention rather than the more clinically relevant issue of resolution of an existing thrombus. In this issue of Blood, Zhang and colleagues 1 describe a novel and effective therapeutic strategy for clearance of preexisting arterial thrombus in murine models of ischemic stroke.